Heart rate variability in type 2 diabetic subjects randomized to liraglutide or glimepiride treatment, both in combination with metformin: A randomized, open, parallel‐group study - Nyström, Thomas; Santos‐Pardo, Irene; Fang, Xin; Cao, Yang; Hedberg, Fredric; Jendle, Johan (Endocrinology, diabetes & metabolism, 2019)
Summary Aims Reduced heart rate variability (HRV) and increased heart rate (HR) are associated with cardiovascular (CV) mortality. In the Liraglutide Effect and Action in Diabetes outcome trial, it was demonstrated a lower rate of CV events in type 2 diabetes (T2D) patients treated with liraglutide compared to placebo. We aimed to investigate the effects of liraglutide compared with glimepiride treatment in T2D patients on the CV risk parameters HR and HRV. Methods This was a post hoc study whereas sixty‐two T2D individuals (45 males) were randomized to once daily 1.8 mg liraglutide or once daily 4 mg glimepiride, both in combination with 1 g metformin. HR and measurement of sympathetic activity, that is standard deviation (SD) of beat‐to‐beat (NN) intervals (SDNN), was assessed by 24‐hour Holter monitoring system. Parasympathetic activity was analysed by root mean square of successive differences (RMSSD) in NN intervals and high‐frequency (HF), low‐frequency (LF) and very low‐frequency power. Results Baseline clinical characteristics for liraglutide (n = 33) and glimepiride (n = 29) groups were well matched. There was a persistent increase in diurnal HR followed by a significantly increased HR at daytime 5.4 beats per minute, P = 0.011 in the liraglutide‐treated group. There was no treatment change between groups in SDNN and RMSSD, or in HF and LF frequency power analysis. Conclusions Liraglutide treatment increased diurnal variation in hourly mean HR followed by an increase in mean daytime HR, independently of changes in sympathetic or parasympathetic activity. We aimed to investigate the effects of liraglutide compared with glimepiride treatment in type 2 diabetes patients on the cardiovascular risk parameters heart rate (HR) and heart rate variability (HRV). Liraglutide treatment increased diurnal variation in hourly mean HR followed by an increase in mean daytime HR, independently of changes in sympathovagal balance.